Fixed Points of Multivalued G-Nonexpansive Mappings in Hadamard Spaces Endowed with Graphs - Bancha Panyanak (Journal of Function Spaces)
A fixed-point theorem for multivalued G-nonexpansive mappings in Hadamard spaces is proved. The strong convergence theorems of Browder’s and Halpern’s iterations are also established. Our results generalize and improve the results of Tiammee et al. (2015), Alfuraidan and Khamsi (2015), Anakkamatee and Tongnoi (2019), and many others.